2019
DOI: 10.1038/s41598-019-40719-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of androgen receptor gene aberrations in circulating cell-free DNA as a biomarker for treatment of castration-resistant prostate cancer

Abstract: The therapeutic landscape of castration-resistant prostate cancer (CRPC) has rapidly expanded. There is a need to develop noninvasive biomarkers to guide treatment. We established a highly sensitive method for analyzing androgen receptor gene (AR) copy numbers (CN) and mutations in plasma circulating cell-free DNA (cfDNA) and evaluated the AR statuses of patients with CRPC. AR amplification was detectable in VCaP cell line (AR amplified) genomic DNA (gDNA) diluted to 1.0% by digital PCR (dPCR). AR mutation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
3
47
2
Order By: Relevance
“…10,17 Additionally, there have been particular pathogenic missense mutations in the ligand-binding domain of AR known to be associated with a worse PSA response and PFS depending on the specific ARTA used. 10,17,18 These findings are promising and should be further validated in future studies. However, screening these gene alterations might not be useful in determining whether to use ABI or ENZ, because resistance mechanisms for ARTAs are similar for ABI and ENZ.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…10,17 Additionally, there have been particular pathogenic missense mutations in the ligand-binding domain of AR known to be associated with a worse PSA response and PFS depending on the specific ARTA used. 10,17,18 These findings are promising and should be further validated in future studies. However, screening these gene alterations might not be useful in determining whether to use ABI or ENZ, because resistance mechanisms for ARTAs are similar for ABI and ENZ.…”
Section: Discussionmentioning
confidence: 65%
“…Genetic alterations detected in circulating tumor DNA will be of help in determining treatment choice for patients with CRPC, 10,17,18 although it is yet to be widely available in real-world clinical practice. Alterations in driver genes including TP53, RB1, PTEN, and AR have been reported to predict unfavorable survival in patients with CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…In three cohorts of patients—CTC - , CTC + /AR7 - , and CTC + /AR-V7 + —outcomes were best for the CTC - cohort, intermediate for CTC + /AR-V7 - patients, and worse for CTC + /AR-V7 patients [226]. Other recent studies have confirmed the clinical utility of AR-V7 detection in ct-DNA as a biomarker for treatment of CRPC [227,228]. Finally, recent studies have also shown that the testing of AR-V7 mRNA in circulating tumor cells may provide an AR-V7-positive and AR-V7 negative score in a clinically acceptable time range and may provide a guide for the choice of the optimal treatment [229].…”
Section: Most Recurrent Genetic Abnormalities Observed In Prostatementioning
confidence: 99%
“…It is reasonable to suggest that AR copy number gain evolves during treatment leading to cross-resistance between next generation ARTAs. Sumiyoshi et al reported that AR aberrations were only associated with poor response to abiraterone, but not to enzalutamide [101]. Recent data suggest that patients with AR gain should be treated with docetaxel [102].…”
Section: Cell-free Dnamentioning
confidence: 99%